PORTRAYING EDUCATOR’S UTILIZATION OF TECHNOLOGY IN POST-PANDEMIC ERA: A PILOT STUDY - Marisca Revani Putri (Nusantara Hasana Journal, 2023)
This study is a pilot study that the aimed to capture an initial condition of educators in Indonesia towards the utilization of technology in post-pandemic era nowadays. There were 30 participants in this pilot study. The participants were educators who are varied in background. The participants are teachers, lecturers, and practitioners in the education sector. A brief survey was conducted on 24 August 2023 in order to capture the challenges faced by the educators in utilizing the technological tools in the classroom or during the teaching-learning process; to know the educator’s familiarity with technological tools that are commonly used in the teaching-learning process; and to gain data of what technological tools have been used by the educators up till this time. This pilot study found that there were 12 challenges faced by the educators in utilizing the technological tools in the classroom or during the teaching-learning process. And it was concluded that all educators have utilized various technological tools that enable the students to have better learning experience in the classroom, especially in assessment phase.